Prevention of Early Postoperative Decline (PEaPoD): protocol for a randomized, controlled feasibility trial - O’Gara, Brian; Marcantonio, Edward R.; Pascual-Leone, Alvaro; Shaefi, Shahzad; Mueller, Ariel; Banner-Goodspeed, Valerie; Talmor, Daniel; Subramaniam, Balachundhar (Current controlled trials in cardiovascular medicine, 2018)
Background Delirium is associated with a significantly increased risk of postoperative morbidity and mortality. Furthermore, delirium has been associated with an increased risk of prolonged cognitive deficits and accelerated long-term cognitive decline. To date, experimental interventions for delirium have mainly focused on alternative pharmacologic and behavioral strategies in the postoperative period. Few studies have examined whether proactive strategies started before surgery can prevent delirium or reduce its sequelae. Neurocognitive training programs such as Lumosity have been shown to be effective in increasing cognitive performance in both elderly healthy volunteers and patients suffering from a myriad of acute and chronic medical conditions. When initiated in the preoperative period, such training programs may serve as interesting and novel patient-led interventions for the prevention of delirium and postoperative cognitive decline (POCD). We hypothesize that perioperative neurocognitive training is feasible in the older cardiac surgical population and are testing this hypothesis using a randomized controlled design. Methods The Prevention of Early Postoperative Decline (PEaPoD) study is a randomized, controlled trial with a target enrollment of 45 elderly cardiac surgical patients. Subjects will be randomized in a 1:1 ratio to undergo either at least 10 days of preoperative neurocognitive training, continued for 4 weeks postoperatively, or usual care control. The primary outcome, feasibility, will be assessed by study recruitment and adherence to protocol. Secondary outcomes will include potential differences in the incidence of postoperative in-hospital delirium and POCD up to 6 months, as determined by the Confusion Assessment Method and the Montreal Cognitive Assessment. Discussion PEaPoD will be the first trial investigating the use of perioperative cognitive training to potentially reduce delirium and POCD in the cardiac surgical population. Information gleaned from this feasibility study will prove valuable in designing future efficacy studies aimed at determining whether this low-risk, patient-led intervention can reduce serious postoperative morbidity. Trial registration ClinicalTrials.gov, NCT02908464 . Registered on 21 September 2016.